The ethics of using placebo in randomised controlled trials: a case study of a Plasmodium vivax antirelapse trial - Cheah, P; Steinkamp, N; von Seidlein, L; Price, R (BioMed Central, 2018)
Background The use of placebos in randomised controlled trials is a subject of considerable ethical debate. In this paper we present a set of considerations to evaluate the ethics of placebo controlled trials that includes: social value of the study; need for a randomised controlled trial and placebo; standards of care; risks of harm due to administration of placebo and the harm benefit balance; clinical equipoise; and double standards. We illustrate the application of these considerations using a case study of a large ongoing multicentre, placebo-controlled, double-blinded, randomised trial to determine primaquine anti-relapse efficacy in vivax malaria. Main Body There is an urgent need for primaquine anti-relapse studies in order to rationalise the management of a potentially fatal disease. An ethical justification for the use of the placebo arm is provided on the grounds that the actual current applied standard of care in most endemic places does not include primaquine. It has also been argued that there is clinical equipoise among the primaquine study arms and that the risk of harms of being in the placebo arm is the risk of having relapse, which is no more than not being included in the trial, and that there are no double standards. Conclusion Based on our set of considerations, we conclude that a placebo arm is not only justified but imperative in this study. We propose that similar considerations should be prospectively applied to other placebo controlled trials and observational control arms where no treatment is offered.